Enterprise vs. product logic: the industrial reorganisation corporation and the rationalisation of the British electrical/electronics industry. Issue 7 (3rd October 2019) - Gandy, Anthony; Edwards, Roy
Abstract: This article examines how the corporate economy was shaped by government intervention through the facilitation of mergers by the Industrial Reorganisation Corporation (IRC) during the late 1960s. We focus on the IRC-led realignment of the electrical/electronics sector applying a conceptual framework to archival material relating to this sector. We find evidence that the mergers were informed by an enterprise-level view of the market while disregarding product-level decision-making and conclude that the IRC vision for the sector widely ignored the product-level logic associated with the designing, making and selling functions. Instead, they relied on assessments of enterprise-level management character.